Subcutaneous Human Dirofilariasis A Rare Case Report from Mumbai, Maharashtra - Sarda, Neha Rahul; Patil, Ketaki Kishor (Annals of Pathology and Laboratory Medicine, 2023)
Subcutaneous human dirofilariasis is caused by the zoonotic filariae, Dirofilaria repens. The frequency of reports is increasing in literature during the last few years and is considered by some authors as an emerging zoonosis.In India, majority of the cases have been reported from Kerala, case reports from other parts of the country is rare. Here, we report a case to focus attention on this rare cause of a subcutaneous nodule which is often misdiagnosed or overlooked. We report a rare case of subcutaneous Dirofilariasis from Mumbai, Maharashtra. A 15-year-old boy who experienced a cosmetic subcutaneous cheek swelling on the left side of face, since 1.5 years. No pain, no sinus and no discharge. A complete hemogram was done which was normal. No eosinophilia was seen. Since the clinical diagnosis was a soft tissue lesion, a radiograph was not taken. The lesion was excised under local anaesthesia, which revealed a filarial nematode compatible with adult gravid female of the Dirofilaria repens, a zoonotic filariasis that causes subcutaneous dirofilariasis in dogs and cats.